Longitudinal study of microphthalmia in connexin 50 knockout mice using spectral-domain optical coherence tomography - Painter, Taishi; Ou, Chenxi; Gong, Xiaohua; Xia, Chun-hong (Frontiers in Ophthalmology, 2024)
Connexin 50 (Cx50) mediated signaling is essential for controlling the lens growth and size. Cx50 mutations cause microphthalmia, smaller lenses, and cataracts in humans and animals. These ocular defects have never been investigated in live Cx50 mutant mice by using non-invasive imaging techniques. Here, we report a longitudinal study of the ocular defects in Cx50 knockout (Cx50KO) mice from the ages of 3 weeks to 12 months by using spectral-domain optical coherence tomography (SD-OCT). The anterior chamber depth (ACD), lens thickness (LT), vitreous chamber depth (VCD), and axial length (AL) were measured along the visual axis and adjusted with corresponding refractive indices. The SD-OCT image data confirm age-related reductions of LT and AL in live Cx50KO mice compared to age-matched wild-type (WT) controls, and the reduction values are comparable to the in vitro measurements of Cx50KO eyeballs and lenses reported previously. Moreover, reductions of ACD were observed in Cx50KO mice at all ages studied while VCD changes are statistically insignificant in comparison to the WT controls. Therefore, Cx50KO’s microphthalmia with small lens is selectively associated with delayed ACD development but not the vitreous formation. This work supports the notion that lens size and/or growth is important for anterior chamber development.